IMPLEMENTASI DATA MINING NAÏVE BAYES DAN SVM (SUPPORT VECTOR MACHINE) DALAM PENGUMPULAN BERITA KRIMINAL DI INDONESIA PADA MASA PANDEMI COVID-19 Studi Kasus : Situs Berita Detik.com: Indonesia - Ufil (J-ENSITEC, 2022)
The intensity of crime news is relatively high, making the public familiar with criminal cases ranging from corruption, drugs, gambling, immoral acts, theft, fraud, and kidnapping to murder. The media are not only reporting or informing of criminal acts that occur, but the media also acts as a tool of social control. Currently, many news sites provide information related to events and phenomena. On the other hand, the Covid-19 pandemic has created multidimensional crises and problems. One of them is the emergence of crime in the community. This study aims to collect criminal news from news sites during the Covid-19 pandemic. It can be analyzed regarding the possibility of a trend of criminal events in tandem with the direction of the Covid-19 pandemic in Indonesia. The news site used in this research is detik.com.